Melaksanakan Perintah Jabatan Sebagai Alasan Penghapusan Pidana Dalam Perkara Tindak Pidana Korupsi (Studi Putusan Nomor 3849 K/Pid.Sus/2019) - Prasetya, Arya; Simangunsong, Frans (Journal Evidence Of Law, 2023)
Corruption is a disgraceful act aimed at financially benefiting oneself, one's family, or a group, which involves state administrators. Various arguments were put forward by the Defendant in the corruption case so that the judge set an acquittal. One of the reasons is the reason for criminal abolition. In decision Number: 3849 K/Pid.Sus/2019, the convict received an acquittal by the judge and one of the considerations was that the convict carried out an order of office. The lack of standard uniformity regarding carrying out this position order is one of the reasons for the failure of the prosecution of defendants in corruption cases. The results of the study concluded Article 51 paragraph (1) of the Criminal Code is the basis for eliminating criminal liability for an act (justifying reasons) for carrying out a valid position order, while Article 51 paragraph (2) of the Criminal Code is the basis for eliminating criminal responsibility to the perpetrator (forgiveness reasons). in good faith thinks that the order is based on a lawful order within his authority. In Article 2 paragraph (1) and Article 3 of the Corruption Law, a person who has been proven to have committed an act of corruption to benefit himself or another person or a corporation, abuses the authority, opportunity, or means available to him, position or position which can harm or means who has a position or position in the state economy.